2021
DOI: 10.3390/ani11092523
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Fauna of the Dusky Grouper (Epinephelus marginatus, Lowe 1834) from the Central Mediterranean Sea

Abstract: This study aimed to investigate parasite fauna of E. marginatus from the central Mediterranean Sea between Messina and Syracuse. In the present survey; parasite fauna of dusky grouper was investigated for two main reasons: the economic value of this species and the current lack of studies regarding the capture area. Seventy dusky groupers were caught from May 2018 to February 2020. Forty-seven out of the 70 specimens (67.2%) were infected with one or more parasite species. The most abundant species was Prosorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Thus, the same parasitological lesions were observed on E. marginatus from several localities of the western Mediterranean Sea (Panebianco et al, 1995;Azzurro et al, 2002;Polinas et al, 2018). Recently, De Benedetto et al (2021) found the infection also in fish from central Mediterranean Sea and ascribed it to Didymodiclinus sp.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Thus, the same parasitological lesions were observed on E. marginatus from several localities of the western Mediterranean Sea (Panebianco et al, 1995;Azzurro et al, 2002;Polinas et al, 2018). Recently, De Benedetto et al (2021) found the infection also in fish from central Mediterranean Sea and ascribed it to Didymodiclinus sp.…”
Section: Introductionsupporting
confidence: 59%
“…Recently, De Benedetto et al . (2021) found the infection also in fish from central Mediterranean Sea and ascribed it to Didymodiclinus sp.…”
Section: Introductionmentioning
confidence: 98%
“…On the coast of Libya, dusky groupers have been reported to exhibit skin lesions and dermatitis, which are most likely caused by parasites. In the Adriatic Sea, trematodes firmly attached to the gills, pseudobranchs, and orobranchial chambers of dusky groupers have also been reported by De Benedetto et al [16].…”
Section: Introductionsupporting
confidence: 58%
“…The tiger grouper (Epinephelus fuscoguttatus) is widely farmed in the subtropical sea areas of the Indian Ocean and the Pacific Ocean [1]. However, the increase in the prevalence of diseases associated with bacteria, viruses, and parasites has hampered the development of grouper culture, resulting in mass economic losses in the industry [2][3][4][5]. The current therapeutic agents for the above-mentioned diseases are mainly antibiotics and chemical agents.…”
Section: Introductionmentioning
confidence: 99%